La inejecutabilidad de las conciliaciones y los derechos indisponibles. - Amaguaña Guarnizo, Jennifer Nataly (2023)
The lack of execution of conciliations is a current reality when it comes to favoring the fulfillment of unavailable rights of all enforceable scope, however this study seeks to establish the considerations and implications in the different legal areas, because although it is true, Ecuador is a country that welcomes in its doctrine undeniable regulations that should provide compliance and respect for the rights of all people, in certain areas is evident the lack of compliance, even more so when in the country governs the Law of arbitration and mediation, In this sense, this research work seeks to analyze the unenforceability of conciliations and the unavailability of rights, through a process of case analysis to ensure the effective enjoyment of the rights of Ecuadorians, through a qualitative-bibliographic methodology, where three cases are analyzed in which the importance of following the due process in each particular case is detailed to ensure the rights of the interested parties.